Information Communication Technology (ICT), In-Service Training And Job Performance Of Public Secondary School Teachers In Calabar Municipality Of Cross River State, Nigeria. - Melvina N. Amalu; Margaret E. Oyo-Ita (Universitas Negeri Makassar, 2023)
The study investigated the contribution of Information Communication technology (ICT), in- service training to job performance public secondary schools teachers in Calabar Municipality of Cross River State, Nigeria. The survey research design was adopted and two hypotheses were formulated to direct the study. The population consisted of 876 teachers from sixteen secondary schools in Calabar Municipality. A simple random sampling technique was used to draw out of a hat to obtain a sample of 219 teachers who constitute 25% of the total population of the study. The instrument used for data collection was a structured questionnaire titled “Educational Support Services and Teachers’ Job Performance Questionnaire” (ESSTJPQ). The instrument's reliability was determined using the Cronbach Alpha method, and the reliability coefficient estimate obtained ranged from 0.77 to 0.88. Data generated were analysed using simple regression analysis. The results revealed that there is a significant relationship between Information and Communication Technology (ICT) and in-service training and job performance of public secondary schools teachers in Calabar Municipality of Cross River State. It was recommended among others that there should be adequate provision of ICT facilities in all schools to boost teachers’ skills in teaching and learning.